Mapping the Intersections: History, Religion, Culture, Governance and Economics in Taraba North Senatorial Zone, Nigeria - Bello Ali; Salihu Lawal (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
This paper offers a comprehensive analysis of the religious, socio-cultural, political, and economic intricacies within the Taraba North Senatorial Zone in Nigeria, with a particular focus on its diverse ethnic groups. The study utilizes a qualitative analysis approach, drawing insights from scholarly literature and interviews with community members. By identifying common themes across different ethnic groups, the paper aims to illuminate the factors shaping social cohesion, governance dynamics, and economic development in the zone. The findings highlight the rich tapestry of religious beliefs, cultural practices, and economic activities among the ethnic groups, showcasing the coexistence of Islam, Christianity, and indigenous spiritual practices. Governance structures range from theocratic models to decentralized councils of elders, reflecting the autonomy of each ethnic community. Economically, the zone exhibits a mix of traditional agriculture, artisanal crafts, and contemporary pursuits, illustrating the adaptive nature of these communities. The paper emphasizes on the importance of a comprehensive understanding of the socio-cultural, political, and economic dimensions in the Taraba North Senatorial Zone. It finally advocates for inclusive development strategies that respect cultural diversity and empower local communities.